Produção recombinante e estudos funcionais de uma cisteíno peptidase de Xanthomonas citri subspécie citri - Silveira, Rosseli Santos da (2009)
The citrus canker disease is caused by a phytopathogenic bacterium Xanthomonas citri ssp. citri (Xac). The common symptoms are defoliation, twig die-back and premature fruit drop. The infection process of this bacterium is not totally elucidated although it has been reported that peptidases are involved in the infection and virulence process. The genome sequencing of the bacterium Xanthomonas citri ssp. citri enabled the detection of a gene that encodes an enzyme cysteine peptidase like, possibly involved in infection. Aiming to characterize this enzyme and determine its possible involvement in the infection process were performed: expression in recombinant Pichia pastoris, purification of protein and enzyme studies for characterization were done. The kinetic characterization of recombinant enzyme was performed through the hydrolysis of synthetic substrates Z-Leu-Arg-MCA and Z-Phe-Arg-MCA (Z = Carbobenzoxy; MCA = 7-amido-4-methylcoumarin), as well as the use of substrates with intramolecular fluorescence suppression AbzKVRSSKQEDDnp, AbzKLRSSKQ-EDDnp and AbzKIRSSKQ-EDDnp (ABZ = Ortoaminobenzoic acid; EDDnp = Ethylene diamine [2,4-dinitrophenyl]). The best catalytic efficiency (Kcat/Km) of the enzyme was found using the substrate AbzKIRSSKQ-EDDnp that has a isoleucine residue at position P2, showing that the recombinant enzyme (HISCPXAC) prefer aliphatic amino acid residue in this position. Inhibitory experiments of enzyme activity were performed using different cysteine peptidase inhibitors including CaneCPI-1, CaneCPI-2, CaneCPI-3, CaneCPI-4 and E-64 (L- transepoxysuccinyl-leucylamido-[4- guanidino]butane), resulting in a constant of inhibition (Ki) of 84.64, 0.088, 0.10, 0.012 and 1.214 nM respectively. The polyclonal antibody anti- HISCPXAC was produced in mouse and Western blotting analysis revealed that the antibody was able to recognize the recombinant purified cysteine peptidase and also the native cysteine peptidase from Xanthomonas citri ssp. citri strain 306 cultivated in media inductor of pathogenicity. The same antibody did not recognize the protein in a Xac knockout strain for the cysteine peptidase gene. Our results suggest that the cysteine peptidase from Xanthomonas citri ssp. citri may be involved in the bacteria infection and/or virulence.